Risk Factors for Anemia in Pregnant Women in Rural Areas: Faktor Risiko Anemia pada Ibu Hamil di Wilayah Pedesaan - Mellinda; Iskandar Arfan; M. Taufik (Indonesian Journal of Administration and Health Research (IJAHR), 2024)
Anemia in pregnant women has a negative impact on both mother and fetus. The purpose of this study was to determine the risk factors for the incidence of anemia in pregnant women in the working area of the balai sepuak health center. This study used an analytic observational design with a case control approach. The population in this study amounted to 289 people. The sample in this study amounted to 62 people who were divided into two groups, namely the case group 31 people and the control group 31 people. Data analysis used chi-square test with 95% confidence level. The results showed that there was a significant relationship between knowledge (p value=0.000), fe tablet consumption (p value=0.010), husband support (p value=0.000), and ANC visits (p value=0.002), with the incidence of anemia in pregnant women. Unrelated variables were maternal age, parity, gestational age, and distance traveled. It is recommended to the health workers of Balai Sepuak Health Center to conduct socialization activities in the community, especially to pregnant women about the incidence of anemia in pregnant women and the impact of anemia on pregnancy, so that it is expected to overcome the incidence of anemia in pregnant women in the puskesmas working area.Anemia pada ibu hamil berdampak buruk bagi ibu maupun janin. Tujuan Penelitian ini untuk mengetahui faktor risiko kejadian anemia pada ibu hamil di wilayah kerja puskesmas balai sepuak. Penelitian ini menggunakan desain observasional analitik dengan pendekatan case control. Populasi dalam penelitian ini berjumlah 289 orang. Sampel dalam penelitian ini berjumlah 62 orang yang dibagi menjadi dua kelompok yaitu kelompok kasus 31 orang dan kelompok kontrol 31 orang. Analisis data menggunakan uji chi-square dengan tingkat kepercayaan 95%. Hasil penelitian menunjukan bahwa terdapat hubungan yang signifikan antara pengetahuan (p value=0,000), konsumsi tablet fe (p value=0,010), dukungan suami (p value=0,000), dan kunjungan ANC (p value=0,002), dengan kejadian anemia pada ibu hamil. Variabel yang tidak berhubungan yaitu umur ibu, paritas, jarak kehamilan, dan jarak tempuh. Disarankan kepada petugas kesehatan Puskesmas Balai Sepuak untuk melakukan kegiatan sosialisasi dimasyarakat khususnya kepada ibu hamil tentang kejadian anemia pada ibu hamil serta dampak dari anemia pada kehamilan, sehingga diharapkan dapat mengatasi kejadian anemia pada ibu hamil di wilayah kerja puskesmas.